Manajemen Pembelajaran Berbasis Camtasia Studio Dalam Mewujudkan Mutu Pendidikan SMP - Anastasia Maing; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2022)
This study is aimed at Describing the learning management based on Camtasia Studio in SMPN 2 East Adonara, Investigating strength and weakness of learning management base on Camtasia Studio, investigating effectiveness of learning management base on Camtasia Studio in the teaching learning process. This study used qualitative research. The techniques used interview, observations, and documentations. The focus of this research was about plan and evaluations in the teaching learning process. The analysis of this research base on Miles & Hubermen analysis method were used reduce, serve a purpose, and verifications. Based on data analysis : the teaching planning base on Camtasia Studio was good and structured. The first planed were determined target and teaching purpose. The teachers’ manner of agglomeration in teaching process were opened step and closed step, so the learning teaching process were organized and directed, in the implementation was fluent, the researcher were prepared manuscript, recording, editing, production and published, the evaluations base on Camtasia Studio were investigated teachers and students obstacles so they could appropriate solution determine for education quality. Keywords: Education Management, Camtasia Studio, Education Quality